Cardiovascular-Specific Mortality among Gastrointestinal Stromal Tumor Patients: A Population-Based Analysis. (14th February 2023) - Yao, Hailing; Shi, Huiying; Fan, Mengke; Yuan, Lanlai; Lin, Rong
Abstract : Background . The overall risk of cardiovascular mortality (CVM) in cancer survivors has increased with time. The trend of CVM in patients with gastrointestinal stromal tumors (GISTs) remains unclear. This study is aimed at assessing the risks and independent predictors of CVM in GIST patients. Methods . Data of the GIST patients were extracted from the Surveillance, Epidemiology, and End Results (SEER) database (2000-2019). The standardized mortality ratio (SMR) was used to evaluate the risk of CVM, and a multivariate competing risk model was utilized to identify the predictors for CVM. Results . A total of 12, 058 patients with GIST were included in this study, of whom 477 (4.0%) patients died of cardiovascular disease (CVD). The SMR for CVM among GIST patients was significantly higher than in the general population (SMR, 3.23, 95% CI: 2.97-3.52), and all categories of CVD were associated with a significantly elevated SMR. The cumulative mortality of CVD was the lowest among all causes of death, while the CVM was the second most common cause of death in patients ≥ 80 years when stratified by age at diagnosis. Furthermore, male sex, older age at diagnosis, White race, unmarried, earlier year of diagnosis, and not receiving chemotherapy were the poor prognostic factors for CVM. Conclusions . The CVM risk in GIST patients was significantly higher relative to the general US population. Timely screening and cardioprotective interventions should be implemented to prevent the occurrence of CVM in patients with GIST.